Greeks and Romans in the Sahara Desert: Ideology and Experience. (1st March 2019) - Reger, Gary
This paper explores tropes about the desert embedded in Greek and Roman literary accounts of interaction with the Sahara Desert, and the ways in which people in the Greek and Roman world who actually lived in desert spaces came to terms with living there - 'normalising' the desert space - while continuing to deploy these standard tropes.